2011
DOI: 10.1105/tpc.110.081414
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional RNA Motif inPotato spindle tuber viroidMediates Trafficking from Palisade Mesophyll to Spongy Mesophyll inNicotiana benthamiana 

Abstract: Cell-to-cell trafficking of RNA is an emerging biological principle that integrates systemic gene regulation, viral infection, antiviral response, and cell-to-cell communication. A key mechanistic question is how an RNA is specifically selected for trafficking from one type of cell into another type. Here, we report the identification of an RNA motif in Potato spindle tuber viroid (PSTVd) required for trafficking from palisade mesophyll to spongy mesophyll in Nicotiana benthamiana leaves. This motif, called lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 93 publications
(118 reference statements)
1
77
0
2
Order By: Relevance
“…This finds support in studies on viroid RNA structures that are specifically necessary for entering specific vascular tissues (Takeda et al, 2011) and in the observed interaction of phloem-delivered mRNAs such as GAI and BEL5 with a phloem-expressed polypyrimidine-tract binding protein (PTB) recognizing poly-cysteine (C)-uracil (U) nucleotide stretches present in the 39 UTRs of some phloem mobile transcripts (Ham et al, 2009;Cho et al, 2015). However, a predicted RNA sequence related to PTB binding motifs was not found in the tRNA fusion constructs used in this study and thus is unlikely to play the primary role in triggering their movement.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This finds support in studies on viroid RNA structures that are specifically necessary for entering specific vascular tissues (Takeda et al, 2011) and in the observed interaction of phloem-delivered mRNAs such as GAI and BEL5 with a phloem-expressed polypyrimidine-tract binding protein (PTB) recognizing poly-cysteine (C)-uracil (U) nucleotide stretches present in the 39 UTRs of some phloem mobile transcripts (Ham et al, 2009;Cho et al, 2015). However, a predicted RNA sequence related to PTB binding motifs was not found in the tRNA fusion constructs used in this study and thus is unlikely to play the primary role in triggering their movement.…”
Section: Discussionmentioning
confidence: 62%
“…Nonconserved viral 39 UTR sequences, which interact with 59 UTRs, seem to play a role in facilitating viral RNA cell-to-cell transfer . Similarly, viroids (infectious, non-protein-coding small RNAs) form specific stem-loop structures not yet identified in other mobile RNAs, allowing them to enter the plant phloem long-distance transport system (Ding, 2009;Takeda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In Potato spindle tuber viroid (PSTVd), cell-to-cell trafficking of viroid RNA was found to be mediated by an RNA structure motif. 36 Whether the endogenous mobile RNA adopts similar structure motifs for long-distance trafficking remains to be investigated.…”
Section: P35s-ft-ir/p35s-rfp-ft P35s-ft-ir/p35s-gfp-ftmentioning
confidence: 99%
“…However, remorin, a Solanaceae protein resident in membrane rafts and plasmodesmata, can interact physically with the MP from Potato virus X and negatively regulates Potato virus X intercellular and phloem-mediated trafficking (Raffaele et al, 2009). Some viral RNAs and viroids also contain important 3D RNA motifs required for intercellular movement (Takeda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%